Comprehensive analysis of the mutation spectrum in 301 German ALS families - Müller, Kathrin; Brenner, David; Weydt, Patrick; Meyer, Thomas; Grehl, Torsten; Petri, Susanne; Großkreutz, Julian; Schuster, Joachim; Volk, Alexander E.; Borck, Guntram; Kubisch, Christian; Klopstock, Thomas; et al. (Journal of neurology, neurosurgery, and psychiatry, 2018)
Objectives Recent advances in amyotrophic lateral sclerosis (ALS) genetics have revealed that mutations in any of more than 25 genes can cause ALS, mostly as an autosomal-dominant Mendelian trait. Detailed knowledge about the genetic architecture of ALS in a specific population will be important for genetic counselling but also for genotype-specific therapeutic interventions. - Methods Here we combined fragment length analysis, repeat-primed PCR, Southern blotting, Sanger sequencing and whole exome sequencing to obtain a comprehensive profile of genetic variants in ALS disease genes in 301 German pedigrees with familial ALS. We report C9orf72 mutations as well as variants in consensus splice sites and non-synonymous variants in protein-coding regions of ALS genes. We furthermore estimate their pathogenicity by taking into account type and frequency of the respective variant as well as segregation within the families. - Results 49% of our German ALS families carried a likely pathogenic variant in at least one of the earlier identified ALS genes. In 45% of the ALS families, likely pathogenic variants were detected in C9orf72, SOD1, FUS, TARDBP or TBK1, whereas the relative contribution of the other ALS genes in this familial ALS cohort was 4%. We identified several previously unreported rare variants and demonstrated the absence of likely pathogenic variants in some of the recently described ALS disease genes. - Conclusions We here present a comprehensive genetic characterisation of German familial ALS. The present findings are of importance for genetic counselling in clinical practice, for molecular research and for the design of diagnostic gene panels or genotype-specific therapeutic interventions in Europe.
Gesehen am 15.07.2021